(untitled) (Research, Society and Development, 2021)
Objective: The article seeks to report the experience lived by participants of the ninth version of PET-Saúde, in a educational workshop on collaborative competence - Patient / User Centered Care. Method: This is a descriptive study, an experience report, carried out by members of the project PET-Saúde Interprofissionalidade an extension program, at Federal University of Maranhão (UFMA), Campus Pinheiro. The educational workshop entitled “Collaborative Competences: Attention Centered on Patient / User”, was offered to 44 participants, including students, teachers and preceptors. Immediate and late (after five months) post-test assessment instruments were applied. Results: It was found that the workshop achieved the expected results, given that in the late questionnaire the participants stated that they obtained and applied knowledge in a satisfactory manner regarding competence worked on. They also claimed an improvement in the relationship between professionals and patients. Conclusion: It is believed that the results of the experiment were satisfactory. Knowledge worked at the Workshop remained present in the interviewees even after five months of their achievement. In addition, the activity allowed a critical analysis of the reality among the participants, encouraging the desire to promote and demonstrate the knowledge acquired on education interprofessional and to carry out a more collaborative practice centered on the patient / user, family and community.